Self-employment in the light of international and union law - Barwaśny, Mateusz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The chapter discusses self-employment in the context of international and Union law. The phenomenon of self-employed activity grows in popularity as a result of massive social and economic as well as technological change. The author presents various definitions of selfemployment and legal guarantees granted under international and Union law to persons who carry out business activity as a self-employed person. It should be noted that no uniform definition of self-employment exists. Moreover, there is no comprehensive approach to or coherent regulations of this matter. Legal rules concerning self-employment are fragmented and often inconsistent. The author points out that international protective standards cover all “working people”. As a result, the self-employed are accorded certain rights in areas such as: life and health, remuneration, nondiscrimination and equal treatment, parenting, rest, and protection of collective interests. Due to the growing popularity of self-employed activity and the significance of human rights, national legislations should grant persons who pursue gainful activity for their own account appropriate protective guarantees. Another important matter is counteracting bogus self-employment, which deprives numerous working people of a proper standard of protection.